27. CURRENT STATUS OF PATIENT SAFETY CULTURE AT THE VIET NAM NATIONAL EYE HOSPITAL IN 2023 AND SOME RELATED FACTORS (Vietnam Journal of Community Medicine, 2024)
Objective: Determining the current state of patient safety culture, helps to better implement patient safety at medical facilitiesResearch methods: Cross-sectional study, combining quantitative and qualitative research through interviewed 500 employees using questionnaires with the HSOPSC.Results: Positive feedback on patient safety culture was 83.3%, reaching a good level. The highest positive feedback in the factor of leader support for patient safety is 95.7% and the lowest positive feedback in the factor of handover and patient transfer is 61.9%. Factors such as medical staff characteristics, hospital management and working environment have a positive influence on patient safety culture.Conclusion: Continue to maintain and implement patient safety quality management programs. Management needs to develop a no-punishment or less-severe message for advisors who report errors to improve the rate of staff and efforts to report the topic.
Keywords: Patient safety culture, factors influencing patient safety culture, Vietnam National Eye Hospital.